China's Wolf Warrior Diplomacy On Social Media In The Era Of Covid-19 - Wiwiek Rukmi Dwi Astuti; Raden Maisa Yudono; Garcia Krisnando Nathanael (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
International communication and diplomacy are significantly influenced by development of technology and communication. The role of diplomats as frepresentatives of the country has been redefined along with public communication activities increasement through social media. This study provides an overview of China's efforts in influencing the formation of public images and opinions through social media carried out by its diplomats. Their aim is to defend China's handling of the COVID-19 pandemic and challenge anyone who questions the events about the issue. This study uses qualitative methods, providing in-depth descriptions through data collection techniques based on internet-based research. This study shows that China is trying to demonstrate hard-line diplomacy called wolf warrior diplomacy. Through social media, Chinese diplomats are seen as government agents who promote national interests of their country, which in this context is related to the COVID-19 pandemic. By acknowledging the term wolf warrior diplomacy, provocative propaganda become a diplomatic tool practiced by Chinese diplomats. China's courage in taking an unconventional approach to the concepts and practices of traditional diplomacy and international communication is seen as part of China's long-term plan.